Tool Demonstration Lamp Gravity (Gravity Lights) - Charla Tri Selda Manik (Journal of Science Technology (JoSTec), 2019)
Petromax lamps have many disadvantages such as kerosene which is increasingly expensive and limited. Petromax lamps also produce pollution in the form of smoke produced which can cause disease. The danger of the petromax lamp is that it can cause a fire if there is negligence. But it is undeniable, people really need lighting from lights, especially at night. Therefore, an alternative plan is needed that can replace the petromax lamp by using other available energy sources. A lamp design using renewable energy that can be used throughout the day without the slightest cost in its use. One of the renewable energies available on earth that can be used to replace petromax lamps is energy that comes from the gravitational force of the earth. Due to the lack of knowledge about the use of gravity as renewable energy, a learning tool is needed that can be used especially by electrical engineering students to better understand the concept of gravity which is applied to a visual aid in the form of a gravity lamp.